Treatment With CD52 Antibody Protects Neurons in Experimental Autoimmune Encephalomyelitis Mice During the Recovering Phase - Hao, Wenlin; Luo, Qinghua; Menger, Michael D.; Fassbender, Klaus; Liu, Yang (Frontiers in Immunology, 2021)
Multiple sclerosis (MS) is a chronic autoimmune disease driven by T and B lymphocytes. The remyelination failure and neurodegeneration results in permanent clinical disability in MS patients. A desirable therapy should not only modulate the immune system, but also promote neuroprotection and remyelination. To investigate the neuroprotective effect of CD52 antibody in MS, both C57BL6/J and SJL mice with experimental autoimmune encephalomyelitis (EAE) were treated with CD52 antibody at the peak of disease. Treatment with CD52 antibody depleted T but not B lymphocytes in the blood, reduced the infiltration of T lymphocytes and microglia/macrophages in the spinal cord. Anti-CD52 therapy attenuated EAE scores during the recovery phase. It protected neurons immediately after treatment (within 4 days) as shown by reducing the accumulation of amyloid precursor proteins. It potentially promoted remyelination as it increased the number of olig2/CC-1-positive mature oligodendrocytes and prevented myelin loss in the following days (e.g., 14 days post treatment). In further experiments, EAE mice with a conditional knockout of BDNF in neurons were administered with CD52 antibodies. Neuronal deficiency of BDNF attenuated the effect of anti-CD52 treatment on reducing EAE scores and inflammatory infiltration, but did not affect anti-CD52 treatment-induced improvement of myelin coverage in the spinal cord. In summary, anti-CD52 therapy depletes CD4-positive T lymphocytes, prevents myelin loss and protects neurons in EAE mice. Neuronal BDNF regulates neuroprotective and anti-inflammatory effect of CD52 antibody in EAE mice.